2012
DOI: 10.1159/000334731
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation of Autosomal-Dominant Corticobasal Degeneration

Abstract: Neurodegenerative tauopathies may be inherited as autosomal-dominant disorders with variable clinicopathological phenotypes, and causative mutations in the microtubule-associated protein tau (<i>MAPT</i>) gene are not regularly seen. Herein, we describe a patient with clinically typical and autopsy-proven corticobasal degeneration (CBD). Her mother was diagnosed to have Parkinson’s disease, but autopsy showed CBD pathology as in the index patient. The sister of the index patient had the clinical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…It has been known for some time that while the characteristic lesions of CBD (tau-positive astrocytic plaques and thread-like lesions in both the white and grey matter) discriminates CBD from the other FTLD-tau subtypes, they do not discriminate sporadic CBD cases from those with MAPT mutations ( Dickson et al , 2002 ) and therefore recent clinical criteria exclude cases with a family history or MAPT mutation from a diagnosis of probable (although not possible) CBD ( Armstrong et al , 2013 ). It has also been long recognized that there is considerable clinical, pathological and genetic overlap between CBD and PSP ( Katsuse et al , 2003 ; Lang, 2003 ; Tan et al , 2005 ; Jung et al , 2012 ) with genome wide association studies showing that common polymorphisms in MAPT , MOBP and VEGFA increase the risk for both CBD and PSP ( Borroni et al , 2010 ; Kouri et al , 2014 , 2015 ). While familial forms of the CBD pathological subtype are recognized ( Dickson et al , 2002 ), familial forms of PSP occur but are considered rare (<10% of cases) ( de Yebenes et al , 1995 ; Rojo et al , 1999 ; Vanacore et al , 2001 ; Ros et al , 2005 ; Donker Kaat et al , 2009 ; Rohrer et al , 2011 ; Fujioka et al , 2015 ), possibly because of the more typical motor phenotype being identified with pathological PSP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that while the characteristic lesions of CBD (tau-positive astrocytic plaques and thread-like lesions in both the white and grey matter) discriminates CBD from the other FTLD-tau subtypes, they do not discriminate sporadic CBD cases from those with MAPT mutations ( Dickson et al , 2002 ) and therefore recent clinical criteria exclude cases with a family history or MAPT mutation from a diagnosis of probable (although not possible) CBD ( Armstrong et al , 2013 ). It has also been long recognized that there is considerable clinical, pathological and genetic overlap between CBD and PSP ( Katsuse et al , 2003 ; Lang, 2003 ; Tan et al , 2005 ; Jung et al , 2012 ) with genome wide association studies showing that common polymorphisms in MAPT , MOBP and VEGFA increase the risk for both CBD and PSP ( Borroni et al , 2010 ; Kouri et al , 2014 , 2015 ). While familial forms of the CBD pathological subtype are recognized ( Dickson et al , 2002 ), familial forms of PSP occur but are considered rare (<10% of cases) ( de Yebenes et al , 1995 ; Rojo et al , 1999 ; Vanacore et al , 2001 ; Ros et al , 2005 ; Donker Kaat et al , 2009 ; Rohrer et al , 2011 ; Fujioka et al , 2015 ), possibly because of the more typical motor phenotype being identified with pathological PSP.…”
Section: Discussionmentioning
confidence: 99%
“…Time of onset of dystonia was provided in only 36 of 111 CBD with dystonia cases 1, 5, 31, 32, 34, 35, 37, 38, 40–45, 47, 51–57, 60, 63, 65, 81. Of these, 52.8% presented dystonia within 2 years from disease onset.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Marshall et al reported a novel heterozygous mutation, p.C291R, with an unusual clinical presentation characterized by progressive apraxia of speech and CBS (Marshall et al, 2015). Although in this family apraxia of speech was the dominant sign, CBS is also known to overlap PPA and FTD and word finding difficulties can be a presenting symptom in CBS (Jung et al, 2012). …”
Section: Discussionmentioning
confidence: 78%
“…Despite having some risk associations with MAPT variants (Jung et al, 2012; Rossi et al 2008; Wischik et al, 2015) pathogenic MAPT mutations are an unusual cause of CBS thus making it hard to define a clear genotype-phenotype correlation.…”
Section: Discussionmentioning
confidence: 99%